Where the Rubber Hits the Road: What Home Healthcare Professionals Need to Know About Driving Safety for Persons With Dementia. (January 2017) - Pastor, Diane K.; Jones, Andrea; Arms, Tamatha
Abstract : Driving cessation for people with dementia is a significant personal safety and public health issue. Home healthcare professionals frequently encounter situations where patients/clients should not continue to drive, and family members are unaware of how to approach the issue. This article will inform readers of the current state of the healthcare driving assessment process, measures and instruments used to assess, and effective strategies and resources when working with families facing the dilemma of how and when to proceed with a driving cessation plan.